Community-Delivered Collaborative and Proactive Solutions and Parent Management Training for Oppositional Youth: A Randomized Trial. Issue 2 (March 2023) - Murrihy, Rachael C.; Drysdale, Sophia A.O.; Dedousis-Wallace, Anna; Rémond, Louise; McAloon, John; Ellis, Danielle M.; Halldorsdottir, Thorhildur; Greene, Ross W.; Ollendick, Thomas H.
Highlights: Collaborative and Proactive Solutions is an effective treatment for defiant youth. Findings were on par with evidence-based treatment, Parent Management Training. Gains were maintained at 6-months follow-up. Community-based delivery affirms relevance to real-world clients and settings. CPS represents a possible therapeutic alternative for youth with conduct problems. Abstract: The aim of this study was to examine the relative effectiveness of Collaborative and Proactive Solutions (CPS) and Parent Management Training (PMT) for youth with oppositional defiant disorder (ODD) in a community setting. Based on a semistructured diagnostic interview, 160 youth with ODD (ages 7–14; 72% male; ethnicity representative of the wider Australian population) were randomized to CPS ( n = 81) or PMT ( n = 79) for up to 16 weekly sessions. The primary hypothesis was that participants in the CPS group, treated in a community setting, would exhibit significant improvement in ODD, equivalent to that of an evidence-based treatment, PMT. Assessment was conducted at baseline, post-intervention, and at 6-month follow-up, using independently rated semistructured diagnostic interviews, parent ratings of ODD symptoms, and global ratings of severity and improvement. Analyses were conducted with hierarchical growth linear modeling, ANCOVA, and equivalence testing using an intent-to-treat sample. Both treatments demonstrated similar outcomes, with 45–50% of youth in the nonclinical range after treatment, and 67% considered much improved. No differences were found between groups, and group equivalency was shown on the independent clinician and parent-rated measures. Gains were maintained at the 6-month follow-up. In conclusion, CPS works as effectively as the well-established treatment, PMT, for youths with ODD, when implemented in a community-based setting. As such, CPS provides a viable choice for families who seek alternate treatments.